Fine tuning of graphene-metal adhesion by surface alloying - Alfè, D.; Pozzo, M.; Miniussi, E.; Günther, S.; Lacovig, P.; Lizzit, S.; Larciprete, R.; Burgos, B. Santos; Menteş, T. O.; Locatelli, A.; Baraldi, A. (Scientific reports, 2013)
We show that bimetallic surface alloying provides a viable route for governing the interaction between graphene and metal through the selective choice of the elemental composition of the surface alloy. This concept is illustrated by an experimental and theoretical characterization of the properties of graphene on a model PtRu surface alloy on Ru(0001), with a concentration of Pt atoms in the first layer between 0 and 50%. The progressive increase of the Pt content determines the gradual detachment of graphene from the substrate, which results from the modification of the carbon orbital hybridization promoted by Pt. Alloying is also found to affect the morphology of graphene, which is strongly corrugated on bare Ru, but becomes flat at a Pt coverage of 50%. The method here proposed can be readily extended to several supports, thus opening the way to the conformal growth of graphene on metals and to a full tunability of the graphene-substrate interaction.